Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1074/jbc.273.10.5735
|View full text |Cite
|
Sign up to set email alerts
|

DNA-mediated Folding and Assembly of MyoD-E47 Heterodimers

Abstract: and ¶Institut fü r Polymere, ETH Zü rich, Switzerland Basic region helix-loop-helix (bHLH) transcription factors regulate key steps in early development by binding to regulatory DNA sites as heterodimers consisting of a tissue-specific factor and a widely expressed factor. We have examined the folding, dimerization, and DNA binding properties of the muscle-specific bHLH protein MyoD and its partner E47, to understand why these proteins preferentially associate in heterodimeric complexes with DNA. In the abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
52
3
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 46 publications
(71 reference statements)
6
52
3
1
Order By: Relevance
“…The presence of a number of residues that were found at high frequency in the HLH domains (Gln 22 and Thr 23 ; Ile 1 , Leu 5 , Met 11 /Val 11 , and Cys 12 ) did not correlate to either greater affinity or specificity to any of the targets, suggesting that these residues have a role in proper folding of the domain and its display on phage coat. The strong bias for the two loop residues Gln 22 and Thr 23 is in agreement with previous work describing the loop as a key determinant of bHLH stability (33). This role is particularly evident for Gln 22 , which occurred in all domains; its structural role is visible in the E47 dimer structure, where it participates, together with Gln 13 and Gln 30 , in a hydrogen bond network that connects the loop with helices 1 and 2, stabilizing the four helix bundle (19).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The presence of a number of residues that were found at high frequency in the HLH domains (Gln 22 and Thr 23 ; Ile 1 , Leu 5 , Met 11 /Val 11 , and Cys 12 ) did not correlate to either greater affinity or specificity to any of the targets, suggesting that these residues have a role in proper folding of the domain and its display on phage coat. The strong bias for the two loop residues Gln 22 and Thr 23 is in agreement with previous work describing the loop as a key determinant of bHLH stability (33). This role is particularly evident for Gln 22 , which occurred in all domains; its structural role is visible in the E47 dimer structure, where it participates, together with Gln 13 and Gln 30 , in a hydrogen bond network that connects the loop with helices 1 and 2, stabilizing the four helix bundle (19).…”
Section: Discussionsupporting
confidence: 75%
“…Thus, they appear to destabilize the dimers. Previous work suggested that heterodimers of MyoD with the E12 E-protein are stabilized by attractive pairs formed by Glu 3 , Glu 7 , and Glu 39 residues of E12 with MyoD residues Arg 29 , Arg 33 , and Gln 39 , respectively (34). Because more stable dimers can be obtained with noncharged amino acids, it seems that the role of the charged Glu residues in the E-protein is to prevent an excessively strong interaction with MyoD or Id2, allowing the physiological partner exchange.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11), which encode both the DNA-binding domain, in the basic region, and the dimerization domain in the HLH region (12). Both E12 and E47 bind the consensus sequence CANNTG as a homodimer or heterodimer with other bHLH proteins, including tissue-specific master genes, such as myogenic differentiation (MyoD) (13).…”
Section: Resultsmentioning
confidence: 99%
“…bHLH-bHLH dimer interactions are strongly stabilized as a ternary complex by DNA binding (43)(44)(45). In order to efficiently sequester bHLH proteins as Id-bHLH heterodimers, Id proteins must be able to overcome the large DNA-binding free energy of bHLH proteins.…”
Section: Discussionmentioning
confidence: 99%